Analysis of OTDR applied to test and diagnosis in PON ODN - Yuehua OU; Yan REN (Dianxin kexue)
The construction scale of optical broadband network brings the massive construction of the access network optic fibers,and the key point is the operation,the maintenance and the management of the network after the large construction,thus it is very important to use highly efficient detection methods and related flexible application methods.Based on the analysis of ODN,the capability of OTDR applied in ODN was analyzed,and the characteristics of ODN key events in the OTDR test was focused,meanwhile according to OTDR detection shortcomings,relevant OTDR application schemes were suggested.